SWOT Analysis Of The Mobile Banking Promotion Strategy At Bank Aceh Syariah - Azra, Feny; Rafiza Zuliani (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
This research aims to find out how strategic the promotion of Bank Aceh Syariah's action is for the people of Aceh Tamiang and to find out the obstacles to promoting Bank Aceh Syariah's action for the people of Aceh Tamiang. The method used is a qualitative approach. Data collection techniques use observation, interviews and documentation. The information in this research is employees of Bank Aceh Syariah, customers of Bank Aceh Syariah Aceh Tamiang. The results of the SWOT analysis show that the strategy that can be used by Bank Aceh is the S-O (strength-opportunity) strategy. The research results show that Bank Aceh Syariah's promotional action strategy uses advertising and personal selling media. The obstacles experienced by Bank Aceh Syariah in promoting action among the people of Aceh Tamiang are the lack of personnel in the promotion department, wide area coverage and network difficulties in several areas in Aceh Tamiang. Keywords: SWOT Analysis; Bank Aceh Syariah; Mobile Banking